ANALISA FAKTOR PENYEBAB DAN AKIBAT CONTRACT CHANGE ORDER PADA PROYEK KONTRUKSI GEDUNG DI KABUPATEN LIMAPULUH KOTA - Fatma Ira Wahyuni; Elvi Syamsyuir; Gusni Vitri (Ensiklopedia of Journal, 2021)
The implementation of construction work is limited by time, quality and cost. There are many problems that can cause changes to work items. In the area of West Sumatra, especially in Limapuluh Kota Regency, in the completion of construction projects, contract change orders often occur. The purpose of this study is to find out what factors are the causes of contract change orders on building construction projects and the impact of change orders on costs and time on building construction projects in Lima Puluh Kota Regency. This research is quantitative. The results of the study found that the causes of contract change orders according to contractors and owners were design changes, work scope changes, work delays, specification changes, work implementation errors, and incompatibility of field conditions with those listed in the contract with different percentages for each. Meanwhile, the effect of CCO on time and cost is with a percentage of <10%.